Proteomics Analysis of Antitumor Activity of Agrimonia pilosa Ledeb. in Human Oral Squamous Cell Carcinoma Cells - Tae-Young Kim; Kwang-Soo Koh; Ji-Min Ju; Yeon-Ju Kwak; Soo-Kyung Bae; Hye-Ock Jang; Da-Sol Kim (Current Issues in Molecular Biology, 2022)
Oral cancer is a malignant neoplasm of oral cavity. It accounts for approximately 5% of all malignant tumors. Approximately 97% of all oral cancers are squamous cell carcinomas, followed by adenocarcinomas, and rarely malignant melanomas. It occurs particularly in males (twice as common in males than in females) of middle age (above 40 years). Agrimonia pilosa Ledeb. has traditionally been known for its effective antitumor activity and is currently used in China for cancer therapy. A. pilosa Ledeb. has been traditionally used for the treatment of abdominal pain, sore throat, headache, blood discharge, parasitic infections, and eczema in Korea and other Asian countries. Most studies on A. pilosa Ledeb. are related to the leaves and a few investigated the roots of the plant. However, detailed mechanisms of antitumor activity of A. pilosa Ledeb. have not been fully elucidated. Furthermore, to date, there have been no reports on the antitumor effect of A. pilosa Ledeb. in oral squamous cells. In this study, we used proteomic technology to observe changes in proteins related to anticancer activity of A. pilosa Ledeb. and identified target proteins among altered proteins to reveal the underlying mechanism of action.